Analysis of eye movements of workers in safe and unsafe behaviors using a video-based method. Issue 1 (2nd January 2023) - Zhu, Ming; Li, Guohui; Huang, Qin; Li, Daiqiang; Du, Junfeng
Abstract : Analyzing eye movements of workers in safe and unsafe behaviors can reduce accidents. With a video-based method, the angular velocity of gaze direction (AVGD) represents micro-movements in gaze and angular velocity in saccade is used to analyze eye movements. A similar behavior simulation experiment is designed to collect operation videos, and an eye movement information extraction and processing framework is constructed to quantify and analyze eye movements. The results show that: the root mean square and movement frequency of AVGD can be used to recognize unsafe behavior; in operations with attention target fixation, compared with safe behavior, workers in unsafe behavior have higher angular velocity, movement frequency and turn frequency of eye movements; and in operations with attention target change, eye movement rules of workers in safe and unsafe behaviors depend on operation types. The results can provide features for unsafe behavior recognition and theoretical bases for safety training.